A cordierite honeycomb ceramic material with low heat capacity and high specific surface area and preparation method thereof

By using materials with narrow particle size distribution spherical magnesium hydroxide, spherical aluminum hydroxide and spherical molten silica, low heat capacity and high specific surface area cordierite honeycomb ceramic materials are prepared, which solves the problems of large extrusion pressure, low body strength and low pore density in the prior art, and achieves an efficient and low cost production process.

CN119219403BActive Publication Date: 2025-03-21SHANDONG AOFU ENVIRONMENTAL PROTECTION SCI & TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718197.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-21
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

During the preparation process, existing honeycomb ceramic materials have problems such as large extrusion pressure, low body strength and low pore density, which are difficult to meet the requirements of low heat capacity and high specific surface area.

Method used

Use spherical magnesium hydroxide, spherical aluminum hydroxide and spherical molten silica as the main raw materials. Low-heat capacity and high specific surface area cordierite honeycomb ceramic materials are prepared through the steps of practice, extrusion, drying and firing to avoid adding pore-forming agents.

Benefits of technology

The preparation of honeycomb ceramic materials with low heat capacity and high specific surface area is realized, which reduces the extrusion pressure, improves the strength and pore density of the blank, and reduces production costs and equipment failure rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219403B_ABST
    Figure CN119219403B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of honeycomb ceramic materials, and in particular to a cordierite honeycomb ceramic material with low heat capacity and high specific surface area and a preparation method thereof. The slurry comprises an inorganic solid component, an organic component and water; the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; the particle size D of the spherical magnesium hydroxide powder with narrow particle size distribution is 50 0.1‑2 μm, particle size D 97 Less than or equal to 20μm; particle size D of spherical aluminum hydroxide powder 50 1‑6 μm, particle size D 97 Less than or equal to 20μm; Spherical fused silica powder particle size D 50 6‑12 μm, particle size D 97 Less than or equal to 20μm, sphericity greater than or equal to 98%. This method has low extrusion pressure, the obtained material has high pore density, and can achieve high porosity without adding pore-forming agents, with ultra-thin walls; it can be applied to various low heat capacity and high specific surface area requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of honeycomb ceramic materials, and in particular to a cordierite honeycomb ceramic material with low heat capacity and high specific surface area and a preparation method thereof. Background Art

[0002] With the upgrading of global emission regulations, the limits of pollutant emissions have been further tightened, and the proportion of pollutant emissions from cold start of motor vehicles in the total pollutant emissions has gradually increased. Therefore, in order to achieve near-zero emissions, it is necessary to improve the conversion efficiency of the catalyst during cold start. In order to improve the conversion efficiency of cold start, the honeycomb ceramic carrier is required to have low heat capacity and high specific surface area. In order to reduce the back pressure of the post-treatment system, the honeycomb ceramic carrier is also required to have low back pressure. In order to achieve low heat capacity and high specific surface area while meeting the requirements of low back pressure, the honeycomb ceramic carrier requires high porosity (lightweight), high pore density, and ultra-thin wall. Such as 600cpsi-4000cpsi, 1-3mil honeycomb ceramic carriers with a porosity of 50-70%.

[0003] With the increase of porosity and the thinning of wall thickness, the conventional preparation method, i.e. using flaky talc, kaolin, irregularly shaped alumina, and adding a large amount of organic pore formers, will bring many problems.

[0004] Specifically, as the pore density increases and the wall thickness decreases, the requirements for mud fluidity increase. Sheet-shaped and irregularly shaped raw materials are prone to bridge when forming and extruding high-pore-density and ultra-thin-wall products. The extrusion pressure is high (reaching over 20 MPa) and there are many product defects.

[0005] In order to form high porosity, a large amount of organic pore formers are added. During sintering, the organic pore formers decompose rapidly, generating a large amount of heat, causing a temperature difference between the inside and outside of the honeycomb ceramic carrier, generating thermal stress, and the ultra-thin wall thickness, which weakens the strength of the green body and causes firing cracking. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a cordierite honeycomb ceramic material with low heat capacity and high specific surface area and a preparation method thereof, so as to solve the problems of high extrusion pressure, low green body strength, low pore density and the like in the prior art.

[0007] The technical solution of the present invention to solve the above technical problems is as follows:

[0008] The present invention provides a cordierite honeycomb ceramic material with low heat capacity and high specific surface area, wherein the slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide, spherical aluminum hydroxide and spherical fused silica with narrow particle size distribution;

[0009] The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder50 0.1-2μm, particle size D 97 Less than or equal to 20μm;

[0010] The particle size D of the spherical aluminum hydroxide powder 50 1-6μm, particle size D 97 Less than or equal to 20μm;

[0011] The particle size D of the spherical fused silica powder 50 6-12μm, particle size D 97 Less than or equal to 20μm, sphericity greater than or equal to 98%.

[0012] Based on the above technical solution, the present invention can also be improved as follows.

[0013] Furthermore, in the narrow particle size distribution spherical magnesium hydroxide powder, the mass percentage of magnesium oxide is greater than or equal to 61.0%, and the mass percentage of calcium oxide is less than or equal to 0.2%;

[0014] In the spherical aluminum hydroxide powder, the mass percentage of aluminum oxide is greater than or equal to 64.0%, and the mass percentage of sodium oxide is less than or equal to 0.1%;

[0015] In the spherical fused silica powder, the mass percentage of the amorphous phase is greater than or equal to 99.5%, and the mass percentage of silica is greater than or equal to 99%.

[0016] Furthermore, the organic component includes a binder and a lubricant; based on the mass of the inorganic solid component being 100%, the mass percentage of the binder is 6.5%-12%, the mass percentage of the lubricant is 4-8%, and the mass percentage of water is 20%-23%.

[0017] Furthermore, the binder is low-viscosity ammonium carboxymethyl cellulose.

[0018] Furthermore, the viscosity of the low-viscosity ammonium carboxymethyl cellulose is 100-1000 mPa.s.

[0019] Furthermore, the lubricant is a nano-scale paraffin emulsion.

[0020] Furthermore, the particle size of the nano-scale paraffin wax emulsion is 5-10 nm, and the solid mass percentage of the nano-scale paraffin wax emulsion is 60-80%.

[0021] The present invention also provides a method for preparing the cordierite honeycomb ceramic material with low heat capacity and high specific surface area as mentioned above, comprising the following steps: refining, extruding, drying and firing the mud material to obtain the honeycomb ceramic material; the extrusion pressure is 4-8MPa, the firing temperature is 1300-1500°C, and the firing insulation time is 6-10 hours.

[0022] The present invention also provides a honeycomb ceramic catalyst carrier, which is prepared by using the ceramic material as mentioned above.

[0023] Furthermore, the pore density of the honeycomb ceramic catalyst carrier is 600-40000 cpsi and the wall thickness is 1-3 mil.

[0024] The beneficial effects of the present invention are:

[0025] (1) The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention uses spherical magnesium hydroxide and spherical aluminum hydroxide with narrow particle distribution, effectively controlling the content of abnormally coarse and large particle size spherical magnesium hydroxide and spherical aluminum hydroxide, in order to prevent the coarse particles from clogging the mold and causing appearance defects such as missing grids and deformed channels of the product;

[0026] (2) The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention uses spherical magnesium hydroxide powder and spherical aluminum hydroxide powder with narrow particle size distribution as main raw materials. The hydroxide decomposes into highly active oxides, which promotes the nucleation of cordierite and the growth of cordierite crystals. Moreover, a large number of pores are formed after the hydroxide decomposes, and no pore-forming agent needs to be added. A high porosity, high pore density, and ultra-thin wall carrier can be obtained, which is beneficial to reducing production costs and improving the firing qualification rate.

[0027] (3) The cordierite honeycomb ceramic material with low heat capacity and high specific surface area of ​​the present invention, and the spherical inorganic solid components can effectively improve the fluidity of the mud, reduce the extrusion pressure, reduce the equipment failure rate, and improve the molding qualification rate;

[0028] (4) The method for preparing the cordierite honeycomb ceramic material with low heat capacity and high specific surface area of ​​the present invention does not require the addition of pore-forming agents to prepare a high porosity, high pore density, ultra-thin-wall honeycomb ceramic carrier;

[0029] (5) The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention can be applied to various applications requiring low heat capacity and high specific surface area;

[0030] (6) The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention can be used to prepare catalyst carriers in the fields of motor vehicle exhaust, environmental protection, thermoacoustic refrigeration, and thermoacoustic power generation. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The SEM image of the cordierite honeycomb ceramic material with low heat capacity and high specific surface area and the spherical magnesium hydroxide powder with narrow particle size distribution of the present invention;

[0032] Figure 2 The SEM image of the cordierite honeycomb ceramic material with low heat capacity and high specific surface area of ​​the present invention, and spherical aluminum hydroxide powder;

[0033] Figure 3 This is a SEM picture of the cordierite honeycomb ceramic material with low heat capacity and high specific surface area of ​​the present invention, which is the honeycomb ceramic material of Example 7. DETAILED DESCRIPTION

[0034] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0035] The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention comprises a slurry comprising an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with a narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica;

[0036] Narrow particle size distribution of spherical magnesium hydroxide powder 50 0.1-2μm, particle size D 97 Less than or equal to 20μm;

[0037] Particle size D of spherical aluminum hydroxide powder 50 1-6μm, particle size D 97 Less than or equal to 20μm;

[0038] Spherical fused silica powder particle size D 50 6-12μm, particle size D 97 Less than or equal to 20μm, sphericity greater than or equal to 98%.

[0039] The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention uses spherical magnesium hydroxide and spherical aluminum hydroxide with narrow particle distribution, effectively controlling the content of abnormally coarse and large particle size spherical magnesium hydroxide and spherical aluminum hydroxide, in order to prevent coarse particles from clogging the mold, causing appearance defects such as product grid defects and pore deformation; at the same time, in order to obtain high activity, the particle size of spherical magnesium hydroxide and spherical aluminum hydroxide is as fine as possible under the condition that the cost permits. The honeycomb ceramic material of the present invention uses spherical fused silica, and limits its sphericity to be greater than or equal to 98%, which can effectively improve the fluidity of the powder in the mud.

[0040] The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention adopts spherical magnesium hydroxide powder and spherical aluminum hydroxide powder with narrow particle size distribution as main raw materials. The hydroxide is decomposed into highly active oxides, which promotes cordierite nucleation and cordierite crystal growth. Moreover, a large number of pores are formed after the hydroxide is decomposed, and there is no need to add a pore-forming agent. A high porosity, high pore density, and ultra-thin wall carrier can be obtained, which is beneficial to reducing production costs and improving the firing qualification rate.

[0041] In one embodiment of the present invention, the SEM image of the narrow particle size distribution spherical magnesium hydroxide powder is as follows: Figure 1 As shown, the SEM image of spherical aluminum hydroxide powder is as follows Figure 2 shown.

[0042] Preferably, in the spherical magnesium hydroxide powder with narrow particle size distribution of the present invention, the mass percentage of magnesium oxide is greater than or equal to 61.0%, and the mass percentage of calcium oxide is less than or equal to 0.2%, so that the spherical magnesium hydroxide powder with narrow particle size distribution has good reactivity.

[0043] Further preferably, the above-mentioned narrow particle size distribution spherical magnesium hydroxide powder of the present invention is generally synthesized by a hydrothermal method. The spherical magnesium hydroxide synthesized by this method has the advantages of high sphericity, high purity and low calcium oxide content.

[0044] Further preferably, the narrow particle size distribution spherical magnesium hydroxide powder of the present invention has a sphericity greater than or equal to 92%.

[0045] Preferably, in the spherical aluminum hydroxide powder of the present invention, the mass percentage of aluminum oxide is greater than or equal to 64.0%, and the mass percentage of sodium oxide is less than or equal to 0.1%, so that the reaction activity of the spherical aluminum hydroxide powder is high.

[0046] Further preferably, the spherical aluminum hydroxide powder of the present invention is generally synthesized by a hydrothermal method, which has the advantages of high sphericity, high purity and low sodium oxide content.

[0047] Further preferably, the narrow particle size distribution spherical magnesium hydroxide powder of the present invention has a sphericity greater than or equal to 90%.

[0048] Preferably, in the spherical fused silica powder, the mass percentage of the amorphous phase is greater than or equal to 99.5%, and the mass percentage of silicon dioxide is greater than or equal to 99%; the high content of the amorphous phase can keep the content of the cristobalite phase at a low level. The thermal expansion coefficient of the cristobalite phase is very large, and during the sintering process, the cristobalite phase is accompanied by a very large volume change, which will bring about sintering difficulties; when the content of the cristobalite phase is low, it can ensure a high sintering success rate and a low damage rate, and the resulting honeycomb ceramic material has a very low thermal expansion coefficient.

[0049] Preferably, the spherical fused silica powder is prepared by flame spheroidization.

[0050] The low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention has organic components in its mud including a binder and a lubricant; based on 100% of the mass of the inorganic solid component, the mass percentage of the binder is 6.5%-12%, the mass percentage of the lubricant is 4-8%, and the mass percentage of water is 20%-23%.

[0051] Preferably, the binder is low-viscosity ammonium carboxymethyl cellulose; the use of low-viscosity ammonium carboxymethyl cellulose as a binder has the advantages of low viscosity, easy reaction of cellulose with water, good film-forming properties, and is beneficial to improving the plasticity and flowability of the mud.

[0052] Further preferably, the viscosity of low-viscosity ammonium carboxymethyl cellulose (ACMC) is 100-1000 mPa.s; the viscosity is the viscosity obtained by testing when the ACMC is prepared into a 2% by mass aqueous solution at 20°C.

[0053] Preferably, the lubricant is a nano-scale paraffin emulsion; the paraffin particles in the emulsion are nano-scale and can be filled between the raw material particles to play a lubricating role, improve the fluidity of the mud, and reduce the extrusion pressure. At the same time, the paraffin has a low melting and volatilization temperature and is easily decomposed and volatilized at a low temperature stage, which reduces heat accumulation and reduces cracking during burning.

[0054] Further preferably, the particle size of the nano-paraffin wax emulsion is 5-10 nm, and the solid mass percentage of the nano-paraffin wax emulsion is 60-80%.

[0055] The preparation method of the cordierite honeycomb ceramic material with low heat capacity and high specific surface area of ​​the present invention comprises the following steps: preparing, extruding, drying and firing the mud material to obtain the honeycomb ceramic material; the extrusion pressure is 4-8MPa, the firing temperature is 1300-1500°C, and the firing insulation time is 6-10 hours.

[0056] The method of the present invention is used to prepare honeycomb ceramic materials, and no pore-forming agent is needed to prepare high-porosity, high-pore-density, ultra-thin-wall honeycomb ceramic carriers. The spherical inorganic solid components can effectively improve the fluidity of the mud, reduce the extrusion pressure, reduce the equipment failure rate, and improve the molding qualification rate.

[0057] During the preparation process, spherical magnesium hydroxide can decompose at a low temperature of 350-500°C, absorb heat, offset the heat generated by the pyrolysis of organic polymers such as molding aids such as binders, dispersants, lubricants, etc., and reduce the temperature difference between the inside and outside of the honeycomb ceramic carrier. After the decomposition of magnesium hydroxide, the volume shrinks rapidly, which is conducive to the formation of pores. At the same time, the highly active magnesium oxide formed by low-temperature decomposition is conducive to the formation of cordierite grains and promotes crystal growth, reduces the thermal expansion coefficient, and increases the isostatic strength of the honeycomb ceramic carrier.

[0058] Spherical aluminum hydroxide can also be decomposed at low temperature of 300-400℃, absorb heat, offset the heat generated by the pyrolysis of organic polymers such as molding aids such as binders, dispersants, lubricants, etc., reduce the temperature difference between the inside and outside of the honeycomb ceramic carrier, and improve the firing qualification rate. At the same time, the high-activity transition state alumina formed by low-temperature decomposition improves the strength of the green body. After the aluminum hydroxide decomposes, its volume shrinks rapidly, which is conducive to the formation of pores. At the same time, its high activity is conducive to the formation of cordierite grains and promotes crystal growth, reduces the thermal expansion coefficient, and increases the isostatic strength of the honeycomb ceramic carrier.

[0059] Spherical silicon dioxide can be used as a skeleton to fill the pores of spherical magnesium hydroxide and aluminum hydroxide. During sintering, Mg 2+ 、Al 3+ Ions migrate to the molten silica to form cordierite, causing the decomposed active magnesium oxide and aluminum oxide to migrate, leaving a large number of pores, thereby obtaining a high porosity. At the same time, the thermal expansion coefficient of the molten silica is very low, ensuring that even if the cordierite phase is not completely formed and silica remains, the low thermal expansion coefficient is still guaranteed.

[0060] The present invention adopts a conventional low-pressure (4-10MPa) extrusion molding preparation method, breaking through the technical barriers of high-pore density, ultra-thin-wall high-cordierite honeycomb ceramics, with a simple production process and low cost.

[0061] In addition, the preparation method of the present invention uses hydroxide decomposition to produce a large amount of porosity, and does not require the use of a pore-forming agent. Therefore, there is no need to adopt a multi-stage heating or insulation sintering process. The steps are simple and the cost is low. The obtained material has a high pore density, a narrow wall thickness, and a low thermal expansion coefficient.

[0062] In a specific embodiment of the present invention, the specific preparation process is as follows:

[0063] The inorganic solid components and the binder dry powder are mixed for 2-3 hours using an inclined strong mixer to obtain a powder; that is, spherical magnesium hydroxide powder with a narrow particle size distribution, spherical aluminum hydroxide powder, spherical fused silica powder and low-viscosity carboxymethyl cellulose ammonium are mixed.

[0064] The uniformly mixed powder is placed in a kneading machine, and nano paraffin emulsion and purified water are added, and wet-mixed and kneaded for 60-120 minutes to obtain a mud material.

[0065] The clay is evacuated through a clay kneading machine with a vacuum degree of above -0.09MPa, and is kneaded into clay segments with plasticity.

[0066] The mud segments are extruded into a honeycomb structure and microwave dried into a green body.

[0067] The green body is cut into precise sizes, fired, and then cold processed to obtain a cordierite honeycomb ceramic material with low heat capacity and high specific surface area.

[0068] The cordierite honeycomb ceramic material with low heat capacity and high specific surface area of ​​the present invention can be applied to various requirements of low heat capacity and high specific surface area.

[0069] Specifically, the low heat capacity and high specific surface area cordierite honeycomb ceramic material of the present invention can be used to prepare catalyst carriers in the fields of motor vehicle exhaust, environmental protection, thermoacoustic refrigeration, and thermoacoustic power generation.

[0070] Preferably, the catalyst carrier has a diameter of 1-13 inches, a height of 2-12 inches, a pore density of 600-40000 cpsi, and a wall thickness of 1-3 mil.

[0071] There is no particular restriction on the shape of the honeycomb grid in the honeycomb structure. A single hole shape such as triangle, square, hexagon, etc. can be used, or multiple hole shapes such as square, hexagon, asymmetric, etc. can be used. It is not necessary to use a single hole shape in the honeycomb structure, and it is preferred to use, for example, square holes.

[0072] The present invention is illustrated below by means of specific examples.

[0073] The specific formula composition of the mud in each embodiment is shown in Table 1 and Table 2. Among them, the narrow particle size distribution spherical magnesium hydroxide powder is recorded as M1, M2, M3, the spherical aluminum hydroxide powder is recorded as A1, A2, A3, and the spherical fused silica powder is recorded as F1, F2, F3.

[0074] In Table 2, the mass percentages of ACMC, paraffin emulsion and water are based on the mass of the inorganic solid component as 100%.

[0075] The SEM image of the material prepared in Example 7 is as follows Figure 3 shown.

[0076] The comparative example adopts the conventional method of synthesizing cordierite: 41.47% of flaky talc, 42.98% of flaky kaolin, 15.54% of alumina, 40% of pore former (starch or graphite), 10% of high viscosity (6000-10000mPa.s) HPMC, and 8% of soybean oil or tung oil.

[0077] Table 1 Specific composition of inorganic solid components in the mud materials of Examples 1-10

[0078]

[0079] Table 2 Specific composition of inorganic solid components, organic components and water in the mud of Examples 1-10

[0080]

[0081] Table 3 Performance test results of honeycomb ceramic materials of various embodiments and comparative examples

[0082]

[0083] The performance tests were conducted on the honeycomb ceramic materials of the embodiment and the comparative example. The test results are shown in Table 3.

[0084] It can be seen from the test results of Examples 1-10 that as the particle size of spherical magnesium hydroxide, spherical aluminum hydroxide, and spherical silicon dioxide becomes finer, the extrusion pressure increases, but the extrusion pressure decreases, and can all meet the requirements of 4-8MPa. The reason is that the raw material particle size is fine, the specific surface area is large, and the fluidity becomes poor. However, as the specific surface area increases, the reaction activity increases, it is easier to synthesize cordierite, the thermal expansion coefficient decreases, and the thermal shock performance improves; as the pore density increases, the wall thickness decreases, the extrusion pressure increases, but can all meet the requirements of 6-11MPa; as the pore density increases, the wall thickness decreases, and the extrusion qualified rate shows a downward trend, but can reach more than 97%, which is much higher than 93.04% of the comparative example; at the same time, as the particle size of spherical magnesium hydroxide, aluminum hydroxide, and spherical silicon dioxide increases, the porosity increases, and the maximum can reach 68.24%, but the thermal expansion coefficient increases with the increase, but is lower than 0.4×10 -6 The following also meet the requirements of three thermal shock tests at 700°C without cracking, and the performance is far superior to that of the control example.

[0085] The honeycomb ceramic material of the present invention has a pore density of up to 40,000 cpsi and a wall thickness of only 2 mil (Example 1). Compared with the solution using flaky alumina, general magnesium oxide and silicon dioxide, it has a significant improvement and obtains an ultra-high porosity (>65%). At the same time, the thermal expansion coefficient can still be maintained at a low level to meet actual needs.

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 0.12μm, particle size D 97 The particle size D of the spherical aluminum hydroxide powder is 1.24 μm and the sphericity is 92%. 50 1.06μm, particle size D 97 The sphericity is 90%; the particle size D 50 6.04μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 14.89 μm, the sphericity is 100%, and the amorphous phase content is 0%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 16.00%, the mass percentage of the spherical aluminum hydroxide powder is 43.31%, and the mass percentage of the spherical fused silica powder is 40.69%.

2. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 0.12μm, particle size D 97 The particle size D of the spherical aluminum hydroxide powder is 1.24 μm and the sphericity is 92%. 50 2.55μm, particle size D 97 The particle size of the spherical fused silica powder is 5.94 μm and the sphericity is 93%. 50 9.19 μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 18.11 μm, the sphericity is 99%, and the amorphous phase content is 0.25%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 16.28%, the mass percentage of the spherical aluminum hydroxide powder is 42.45%, and the mass percentage of the spherical fused silica powder is 41.27%.

3. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 0.12μm, particle size D 97 The particle size D of the spherical aluminum hydroxide powder is 1.24 μm and the sphericity is 92%. 50 5.98 μm, particle size D 97 The particle size of the spherical fused silica powder is 16.78 μm and the sphericity is 95%. 50 11.96 μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 19.41 μm, the sphericity is 98%, and the amorphous phase content is 0.49%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 16.23%, the mass percentage of the spherical aluminum hydroxide powder is 42.80%, and the mass percentage of the spherical fused silica powder is 40.98%.

4. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 1.02μm, particle size D 97 The particle size D of the spherical aluminum hydroxide powder is 4.22 μm and the sphericity is 95%. 50 1.06μm, particle size D 97 The sphericity is 90%; the particle size D 50 11.96 μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 19.41 μm, the sphericity is 98%, and the amorphous phase content is 0.49%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 16.54%, the mass percentage of the spherical aluminum hydroxide powder is 43.29%, and the mass percentage of the spherical fused silica powder is 40.17%.

5. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 1.02μm, particle size D 97 The particle size D of the spherical aluminum hydroxide powder is 4.22 μm and the sphericity is 95%. 50 2.55μm, particle size D 97 The particle size of the spherical fused silica powder is 5.94 μm and the sphericity is 93%. 50 6.04μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 14.89 μm, the sphericity is 100%, and the amorphous phase content is 0%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 16.80%, the mass percentage of the spherical aluminum hydroxide powder is 42.09%, and the mass percentage of the spherical fused silica powder is 41.11%.

6. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 1.02μm, particle size D 97 The particle size D of the spherical aluminum hydroxide powder is 4.22 μm and the sphericity is 95%. 50 5.98 μm, particle size D 97 The particle size of the spherical fused silica powder is 16.78 μm and the sphericity is 95%. 50 9.19 μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 18.11 μm, the sphericity is 99%, and the content of the amorphous phase is 0.25%; in the inorganic solid component, the mass percentage of the spherical magnesium hydroxide powder with narrow particle size distribution is 16.76%, the mass percentage of the spherical aluminum hydroxide powder is 42.36%, and the mass percentage of the spherical fused silica powder is 40.88%.

7. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 2.00μm, particle size D 97 The particle size of the spherical aluminum hydroxide powder is 5.71 μm and the sphericity is 98%. 50 5.98 μm, particle size D 97 The particle size of the spherical fused silica powder is 16.78 μm and the sphericity is 95%. 50 6.04μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 14.89 μm, the sphericity is 100%, and the amorphous phase content is 0%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 17.56%, the mass percentage of the spherical aluminum hydroxide powder is 41.86%, and the mass percentage of the spherical fused silica powder is 40.58%.

8. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 2.00μm, particle size D 97 The particle size of the spherical aluminum hydroxide powder is 5.71 μm and the sphericity is 98%. 50 2.55μm, particle size D 97 The particle size of the spherical fused silica powder is 5.94 μm and the sphericity is 93%. 50 11.96 μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 19.41 μm, the sphericity is 98%, and the content of the amorphous phase is 0.49%; in the inorganic solid component, the mass percentage of the spherical magnesium hydroxide powder with narrow particle size distribution is 17.63%, the mass percentage of the spherical aluminum hydroxide powder is 41.93%, and the mass percentage of the spherical fused silica powder is 40.44%.

9. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 2.00μm, particle size D 97 The particle size of the spherical aluminum hydroxide powder is 5.71 μm and the sphericity is 98%. 50 1.06μm, particle size D 97 The sphericity is 90%; the particle size D 50 9.19 μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 18.11 μm, the sphericity is 99%, and the amorphous phase content is 0.25%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 17.34%, the mass percentage of the spherical aluminum hydroxide powder is 42.71%, and the mass percentage of the spherical fused silica powder is 39.95%.

10. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area, characterized in that: The slurry of the honeycomb ceramic material comprises an inorganic solid component, an organic component and water; wherein the inorganic solid component comprises spherical magnesium hydroxide with narrow particle size distribution, spherical aluminum hydroxide and spherical fused silica; The inorganic solid component is: The particle size D of the narrow particle size distribution spherical magnesium hydroxide powder 50 2.00μm, particle size D 97 The particle size of the spherical aluminum hydroxide powder is 5.71 μm and the sphericity is 98%. 50 1.06μm, particle size D 97 The sphericity is 90%; the particle size D 50 6.04μm, particle size D 97 The particle size of the spherical magnesium hydroxide powder is 14.89 μm, the sphericity is 100%, and the amorphous phase content is 0%; in the inorganic solid component, the mass percentage of the narrow particle size distribution spherical magnesium hydroxide powder is 17.33%, the mass percentage of the spherical aluminum hydroxide powder is 42.62%, and the mass percentage of the spherical fused silica powder is 40.05%.

11. A cordierite honeycomb ceramic material with low heat capacity and high specific surface area according to any one of claims 1 to 10, characterized in that: In the narrow particle size distribution spherical magnesium hydroxide powder, the mass percentage of magnesium oxide is greater than or equal to 61.0%, and the mass percentage of calcium oxide is less than or equal to 0.2%; In the spherical aluminum hydroxide powder, the mass percentage of aluminum oxide is greater than or equal to 64.0%, and the mass percentage of sodium oxide is less than or equal to 0.1%; In the spherical fused silica powder, the mass percentage of silicon dioxide is greater than or equal to 99%.

12. The low heat capacity and high specific surface area cordierite honeycomb ceramic material according to claim 11, characterized in that: The organic component includes a binder and a lubricant; based on the mass of the inorganic solid component being 100%, the mass percentage of the binder is 6.5%-12%, the mass percentage of the lubricant is 4-8%, and the mass percentage of water is 20%-23%.

13. The low heat capacity and high specific surface area cordierite honeycomb ceramic material according to claim 12, characterized in that: The binder is low viscosity ammonium carboxymethyl cellulose.

14. The low heat capacity and high specific surface area cordierite honeycomb ceramic material according to claim 13, characterized in that: The viscosity of the low-viscosity ammonium carboxymethyl cellulose is 100-1000 mPa.s.

15. The low heat capacity and high specific surface area cordierite honeycomb ceramic material according to claim 12, characterized in that: The lubricant is nano-level paraffin emulsion.

16. The low heat capacity and high specific surface area cordierite honeycomb ceramic material according to claim 15, characterized in that: The particle size of the nano-paraffin wax emulsion is 5-10 nm, and the solid mass percentage of the nano-paraffin wax emulsion is 60-80%.

17. A method for preparing a cordierite honeycomb ceramic material with low heat capacity and high specific surface area according to any one of claims 1 to 16, characterized in that: The method comprises the following steps: preparing, extruding, drying and firing the clay material to obtain the honeycomb ceramic material; the extrusion pressure is 4-8MPa, the firing temperature is 1300-1500°C, and the firing insulation time is 6-10 hours.

18. A honeycomb ceramic catalyst carrier, characterized in that: The method is prepared by using the ceramic material as described in any one of claims 1 to 16.

19. A honeycomb ceramic catalyst carrier according to claim 18, characterized in that: The pore density of the honeycomb ceramic catalyst carrier is 600-40000 cpsi, and the wall thickness is 1-3 mil.

Citation Information

Patent Citations

  • Thermal shock resistant porous ultrahigh-channel ceramic material and preparation method thereof

    CN118993703A

  • Thin wall cordierite carrier for ceramic honeycomb catalyst and method for preparing the same

    CN1827217A